The state of police staffing in the Ukrainian SSR in the mid-1950s. (Law and Safety, 2023)
A topical and insufficiently studied issue in historical and legal science is the question of structural changes in the Ministry of Internal Affairs and their impact on the state of staffing of the police operating in the Ukrainian SSR in the first period after the change of power in the USSR, in the context of partial liberalization of the Soviet totalitarian regime (1954–1955). An analysis of police activity during this period shows that the level of crime prevention was correlated with the level of qualification of police officers. There were significant shortcomings in the work of regional and city police departments in the selection, placement and promotion of police management personnel as this issue was not sufficiently controlled by the republic’s Ministry of Internal Affairs. It has been emphasized that in the mid-1950s, the staffing of the police of the Ukrainian SSR was at a low level. There was a significant turnover of personnel. This was due to mistakes in the selection of personnel to the ranks of this law enforcement body, insufficient verification of their business and moral qualities, and insufficient attractiveness of police service due to low material support and poor living conditions. Professional training for the police was clearly insufficient, and in 1953 a number of regional police schools were closed. The general educational level of police officers was also low, a significant number of them did not even have an incomplete secondary education. At the beginning of 1955, more than 16 % of the police officers of the Ministry of Internal Affairs of the Ukrainian SSR, 7.5 % of the employees of the Department for Combating the Theft of Socialist Property had a secondary education and more than 60 % had incomplete secondary education, and 50 % of the heads of city police stations did not even have a secondary education. In 1955, the state of staffing became the subject of a special discussion at the Board of the Ministry of Internal Affairs of the Ukrainian SSR. Specific shortcomings were identified in the work of personnel departments both in the republican MIA and in the regional departments of the republic. Many of them did not have an effective personnel reserve, which led to significant delays in staffing certain management positions. The resolution identified measures to improve the personnel situation, but they cannot be called sufficiently well-thought-out, however, this resolution of the board played a certain positive role in improving the level of work with personnel in the police of the republic.
Keywords: Ukraine; 1950s; Ministry of Internal Affairs; police; personnel.